Hello.
Firstly, let's isolate x on the equation:
Now, we can replace 'x' for 'y' and vice-versa:
Hope I helped.
Answer:
tn = 8n -7
Step-by-step explanation:
given : t2=9, t4=25
the formula is:
tn = t1 + (n-1) d
gonna find d first:
d = (25-9) /(4-2) = 16/2 = 8
and find tn1:
t1 = 9-8 = 1
so, tn = 1 + (n-1) (8) = 1 +8n -8
tn = 8n -7
Answer:
D) 6.4
Step-by-step explanation:
The Angle Bisector Theorem says that an angle bisector of a triangle will divide the opposite side into two segments that are proportional to the other two sides of the triangle.
This means that:
18/9.6 = 12/x
Solving for x:
x = 12*9.6/18
x = 6.4